3D quantum theranosomes: a new direction for label-free theranostics. Issue 2 (4th December 2018) - Chinnakkannu Vijayakumar, Sivaprasad; Venkatakrishnan, Krishnan; Tan, Bo
Abstract : Quantum-scale materials offer great potential in the field of cancer theranostics. Abstract : Quantum-scale materials offer great potential in the field of cancer theranostics. At present, quantum materials are severely limited due to 0D & 1D materials lacking biocompatibility, resulting in coated materials with labelled tags for fluorescence excitation. In addition, the application of magnetic quantum materials has not been reported to date for cancer theranostics. In this current research study, we introduce the concept of applying nickel-based magnetic 3D quantum theranosomes for label-free broadband fluorescence enhancement and cancer therapy. To begin with, we present two (primary and secondary) distinct quantum theranosomes for cancer detection and differentiation (HeLa & MDAMB-231) from mammalian fibroblast cells. The primary theranosomes exhibit a metal enhanced fluorescence (MEF) property through localized surface plasmon resonance to act as cancer detectors, whereas the secondary theranosomes act as cancer differentiators through the fluorescence quenching of HeLa cancer cells. Apart from the above, the synthesized magnetic quantum theranosomes introduced therapeutic functionality wherein the theranosomes mimicked a tumor microenvironment by selectively accelerating the proliferation of mammalian fibroblasts cells while at the same time inducing cancer therapy. These quantum theranosomes were synthesized using femtosecond pulse laser ablation and self-assembled to form an interconnected 3D structure. The 3D architecture and the physicochemical properties of the laser synthesized quantum theranosomes closely resembled a tumor microenvironment. Furthermore, we anticipate that our current recorded findings can shed further light upon these unique magnetic quantum theranosomes as potential contenders towards opening an entirely new direction in the field of cancer theranostics.